Facilitation of team-based care to improve HTN management and outcomes: a protocol for a randomized stepped wedge trial - Donna R. Shelley; Dominique Brown; Charles M. Cleland; Hang Pham-Singer; Dina Zein; Ji Eun Chang; Winfred Y. Wu (BMC, 2023)
Abstract Background There are well-established guidelines for treating hypertension (HTN), yet only half of patients with HTN meet the defined target of < 140/90. Team-based care (TBC) is an evidence-based strategy for improving blood pressure (BP) management and control. TBC is defined as the provision of health services by at least two health professionals "who work collaboratively with patients and their caregivers to accomplish shared goals to achieve coordinated, high-quality care". However, primary care practices experience challenges to implementing TBC principles and care processes; these are more pronounced in small independent practice settings (SIPs). Practice facilitation (PF) is an implementation strategy that may overcome barriers to adopting evidence-based TBC to improve HTN management in SIPs. Methods Using a stepped wedge randomized controlled trial design, we will test the effect of PF on the adoption of TBC to improve HTN management in small practices (< 5 FTE clinicians) in New York City, and the impact on BP control compared with usual care. We will enroll 90 SIPs and randomize them into one of three 12-month intervention waves. Practice facilitators will support SIPs to adopt TBC principles to improve implementation of five HTN management strategies (i.e., panel management, population health, measuring BP, supporting medication adherence, self-management). The primary outcome is the adoption of TBC for HTN management measured at baseline and 12 months. Secondary outcomes include the rate of BP control and sustainability of TBC and BP outcomes at 18 months. Aggregated data on BP measures are collected every 6 months in all clusters so that each cluster provides data points in both the control and intervention conditions. Using a mixed methods approach, we will also explore factors that influence the effectiveness of PF at the organization and team level. Discussion This study will provide much-needed guidance on how to optimize adoption and sustainability of TBC in independent primary care settings to reduce the burden of disease related to suboptimal BP control and advance understanding of how facilitation works to improve implementation of evidence-based interventions. Trial registration ClinicalTrials.gov; NCT05413252 .